Kajian Natur Siswa sebagai Gambar dan Rupa Allah dalam Pendidikan Kristen yang Holistik [The Study of Students' Nature as the Image and Likeness of God in Holistic Christian Education] - Chindy Mutiara Br Hombing; Yanti Yanti (Diligentia: Journal of Theology and Christian Education, 2023)
The philosophy of Christian education is based on the foundation of restoration of man as the image and likeness of God who fell into sin to be reconciled and redeemed to God. Christian education aims to transform students towards the likeness of God's character. Unfortunately, the practice of Christian education pays less attention to the development of the whole aspects of a student and instead only focuses on particular aspects, so that many students only obtain knowledge, but are lacking character and spiritual life shown in their life. This gap awakens the needs for a holistic approach, namely focusing on all aspects of human life. Therefore, the purpose of this article is to explain the implications of holistic Christian education practices based on the importance of students' natures in achieving the goals of Christian education. The method used here is literature study based on several focus studies, namely philosophical views, students as the image and likeness of God and holistic Christian education. As a result, the existence of holistic students is directed to learning that comes from God's truth through holistic Christian education. The practice of Christian education is recommended to provide teachings that touch the heart to bring humans to recovery towards the right way of life before God. Educational institutions present an integrated curriculum of spiritual aspects to realize a positive response and responsibility of students towards others and nature.BAHASA INDONESIA ABSTRACT: Filsafat pendidikan Kristen mendasari pada pemulihan manusia sebagai gambar dan rupa Allah yang jatuh ke dalam dosa untuk direkonsiliasi, ditebus dan didamaikan dengan Allah. Pendidikan Kristen bertujuan mentransformasi individu secara utuh untuk menuju keserupaan karakter Allah. Faktanya, praktik pendidikan Kristen kurang memperhatikan pengembangan semua aspek dan tidak jarang hanya terfokus pada satu aspek saja, sehingga banyak siswa yang hanya berpengetahuan baik namun karakter dan kehidupan spiritual yang ditunjukkan malah kurang atau buruk. Kesenjangan ini menyadarkan perlunya pendekatan holistik yaitu memberi perhatian kepada seluruh aspek kehidupan manusia. Oleh sebab itu, tujuan penulisan ini yaitu memaparkan implikasi praktik pendidikan Kristen yang holistik berdasarkan pertimbangan pentingnya natur siswa dalam mewujudkan tujuan pendidikan Kristen. Metode yang dipakai adalah studi literatur berdasarkan beberapa fokus kajian yakni tinjauan filosofis, siswa sebagai gambar dan rupa Allah dan pendidikan Kristen yang holistik. Hasilnya, keberadaan siswa yang holistik diarahkan kepada pembelajaran yang bersumber dari kebenaran Allah melalui pendidikan holistik. Praktik pendidikan Kristen disarankan memberikan pengajaran yang sampai menyentuh hati untuk membawa manusia kepada pemulihan menuju cara hidup yang benar di hadapan Allah. Institusi pendidikan menghadirkan kurikulum terintegrasi aspek spiritual untuk mewujudkan respons positif dan tanggung jawab siswa terhadap sesama dan alam.